1998
DOI: 10.1111/1468-0084.00108
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Mobility in Britain: Evidence from Unemployment Patterns

Abstract: Recent papers have examined the intergenerational transmission of well‐being by looking at the relationship between parents' and children's income. However, by concentrating on those who are working these studies exclude some of the very poorest in society, the unemployed. In this paper we extend the empirical work on intergenerational welfare in the UK by looking at the links between fathers' and sons' unemployment histories. Using an approach which takes account of both incidence and intensity of son's unemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…I find that there is indeed a strong correlation: A child who has experienced at least one unemployed parent during his or her teen-age years faces an approximately 50% larger unemployment probability than a child who has not. 1 Other papers on this subject confirm the existence of a substantial intergenerational correlation (O'Neill and Sweetman, 1998;Corak et al 2000;and Österbacka, 2001). This correlation can be partly attributed to observed differences between families, e.g.…”
Section: This Paper Examines the Intergenerational Correlation In Unementioning
confidence: 90%
See 1 more Smart Citation
“…I find that there is indeed a strong correlation: A child who has experienced at least one unemployed parent during his or her teen-age years faces an approximately 50% larger unemployment probability than a child who has not. 1 Other papers on this subject confirm the existence of a substantial intergenerational correlation (O'Neill and Sweetman, 1998;Corak et al 2000;and Österbacka, 2001). This correlation can be partly attributed to observed differences between families, e.g.…”
Section: This Paper Examines the Intergenerational Correlation In Unementioning
confidence: 90%
“…The existing explicit attempts of extracting the causal component from the intergenerational correlation in unemployment are Österbacka (2001) Corak et al (2000) and O'Neill and Sweetman (1998). Österbacka (2001) and Corak et al (2000) both employ the same method, first presented in Gottschalk (1996).…”
Section: Section 2: Identification Strategiesmentioning
confidence: 99%
“…2 Johnson and Reed (1996), Macmillan (2010, 2014), Mäder et al (2014, and O'Neill and Sweetman (1998) study the effect of paternal unemployment on sons, whereas Eckhaugen (2009) analyzes the effect of parental unemployment on sons and daughters. The studies differ in various ways: Johnson and Reed (1996), Macmillan (2010), and O'Neill and Sweetman (1998 age is 14-18 (24-26). Despite these differences, all papers find positive intergenerational correlations but little evidence for a causal effect.…”
Section: Intergenerational Transmission Of Unemploymentmentioning
confidence: 99%
“…Studies on the intergenerational transmission of unemployment (e.g., Eckhaugen 2009, Gregg et al 2012, Maeder et al 2014, Macmillan 2014, O'Neill and Sweetman 1998, Oreopoulos et al 2008) typically report positive intergenerational correlations of unemployment but mixed results on whether there is a causal effect. While the literature analyzing educational outcomes finds negative short-term effects of paternal unemployment (e.g., Rege et al 2011, Gregg et al 2012, Pinger 2012, evidence on longer-run effects exists only for Canada and the U.S. (Coelli 2011, Wightman 2012) and points at a negative causal effect.…”
Section: Introductionmentioning
confidence: 99%
“…dierences in parents' investment in their children's human capital (Blau, 1999). O'Neill and Sweetman (1998) show that the probability to become unemployed is twice as high for a son whose father was unemployed 20 years ago compared to a son whose father has no unemployment experience. Other studies have shown that the reason why parents become unemployed highly matters.…”
Section: Introductionmentioning
confidence: 99%